Electrochemical characterization of Co(II) and Pd(II) phthalocyanines carrying diethoxymalonyl and carboxymethyl substituents - (:unkn) unknown (PLEIADES PUBLISHING INC, 2006)
In this study, electrochemical behaviors of Co(II) and Pd(II) phthalocyanines carrying tetrakisdiethoxymalonyl and Pd(II) phthalocyanine carrying tetrakiscarboxymethyl substituents at the peripheral positions are investigated by cyclic voltammetry and applied potential chronocoulometry techniques. Cyclic voltammetric studies show that, while Pd(II) phthalocyanines carrying diethoxymalonyl and carboxymethyl substituents give up to three common phthalocyanine ring reductions, Co(II) phthalocyanine carrying diethoxymalonyl substituents gives a metal-centered oxidation and a metal-centered reduction and three ligand-centered reduction and a ligand-centered oxidation processes. First reduction processes of both the PdPc complexes have shoulders. This different voltammetric behaviors of Pd(II) phthalocyanines carrying carboxymethyl and diethoxymalonyl substituents results from interaction of this distinctive substituents with the phthalocyanine ring pi electron System and interaction with the different solvent systems. Observation of the splitting of the first reduction process of Pd(II) phthalocyanines carrying diethoxymalonyl and carboxymethyl substituents suggests the aggregation of the complex. Very small diffusion coefficient of the complexes with respect to Co(II) phthalocyanine also confirms the existence of the aggregation of the complex during the electrochemical studies. Effects of the substituents and the solvent media are clearly observed from the differences of the voltammograms of Pd(II) phthalocyanines carrying diethoxymalonyl and carboxymethyl substituents in DMSO and THF solvent media, respectively.
Keywords: electrochemistry; cyclic voltammetry; aggregation; cobalt; palladium; phthalocyanines; metal complexes; PORPHYRAZINES